Deposition, persistence and turnover of pollutants: First results from the EU project AquaTerra for selected river basins and aquifers - Barth, J. A. C.; Steidle, D.; Kuntz, D.; Gocht, T.; Mouvet, C.; von Tümpling, W.; Lobe, I.; Langenhoff, A.; Albrechtsen, H.-J.; Janniche, G. S.; Morasch, Barbara; Hunkeler, Daniel; et al. (My University, 2007)
Deposition, turnover and movement of persistent organic pollutants (POP) were investigated in the EU integrated project “AquaTerra”, which is among the first funded environmental projects within the 6th Framework Program by the European Commission. Project work integrates across various disciplines that range from biogeochemistry, environmental engineering, computer modelling and chemistry to socio-economic sciences. Field study areas are the river basins of the Ebro, the Meuse, the Elbe and the Danube as well as the 3-km2 French catchment of the Brévilles Spring. Within the first 2 years of the project more than 1700 samples of atmospherically deposited particles, sediments, and water have been collected in the above-mentioned systems. Results show clear spatial patterns of deposition of polyaromatic hydrocarbons (PAHs) with the highest rates in the Meuse Basin. For local inputs, in the Brévilles sandy aquifer, the contamination of the groundwater by the pesticides atrazine (AT) and deethylatrazine did not decrease even 5 years after their agricultural inputs were stopped. On the other hand, herbicides such as mecroprop (MCPP), and PAHs, were at least partially degraded microbiologically in laboratory studies with soils and aquifer material from selected sites. For sediment transport of contaminants, new flood sampling techniques revealed highest deposition rates of β-hexachlorocyclohexane (β−HCH) in river sediments at hotspot areas on the Mulde River in the Bitterfeld region (Elbe Basin, Germany). These selected preliminary results of AquaTerra help to improve fundamental understanding of persistent organic pollutants (POP) in the environment.